The downfall of a young entrepreneurial company : a review of its structure, strategy and processes. - Lee, Eng Thye. (2008)
In this thesis, we carry out an in-depth study of a real-life company, Advanced Piling Products Pte Ltd (APP), its structure, strategy and processes, and examine whether there are any misfits among these three elements. This is because organizational survival depends on the quality of this “fit” which management achieves, among variables.